The Nature of Science and Citizenship: a Delphi Analysis - González-García, Francisco José; Blanco-López, Ángel; España-Ramos, Enrique; Franco-Mariscal, Antonio Joaquín (Springer Nature, 2021)
The relationship between science and society has, for many years, been the subject of debate in different fields, and various proposals have been made regarding the kind of science education that citizens require. The present study considers an understanding of the nature of science (NOS) to be one of the key competences that citizens should acquire as part of their science education. Hence, our aim was to identify NOS aspects among the key scientific competences for citizenship identified by a panel of Spanish experts. The analysis is based on a review of the recent literature on the NOS, and especially on the results of a previous Delphi study in which 31 experts were asked to propose key aspects of scientific competence for citizenship. The present study involved three stages: identification of NOS themes in the experts’ initial proposals, analysis of how their importance ratings of these themes changed over the course of the Delphi rounds, and analysis of variability among the experts according to their professional group. We identified 12 NOS themes that, in line with recent publications in this field, included those related to the practice of science. A stable consensus was only observed for one theme: critical attitude. These results provide further evidence of the well-documented difficulty of defining and selecting NOS themes. However, the analysis also suggests that critical attitude is one of the key themes that should form part of science education for citizens.
EDU2017 82197-P
https://openpolicyfinder.jisc.ac.uk/id/publication/16494
Keywords: Ciencia - Aspectos sociales; Divulgación científica; Método Delphi; Nature of science (NOS); Scientific competence; Delphi study; Citizenship